2014
DOI: 10.1039/c4cp01311e
|View full text |Cite
|
Sign up to set email alerts
|

Energy transfer in aggregates of bacteriochlorophyll c self-assembled with azulene derivatives

Abstract: Bacteriochlorophyll (BChl) c is the main light-harvesting pigment of certain photosynthetic bacteria. It is found in the form of self-assembled aggregates in the so-called chlorosomes. Here we report the results of co-aggregation experiments of BChl c with azulene and its tailored derivatives. We have performed spectroscopic and quantum chemical characterization of the azulenes, followed by self-assembly experiments. The results show that only azulenes with sufficient hydrophobicity are able to induce aggregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…To examine absorbance properties of L. deliciosus and L. sanguifluus crude extracts, the adsorption UV-Vis spectra were measured and the obtained spectra in full UV-Vis range are presented in Figure 3. The absorption spectra of natural dyes from L. deliciosus and L. sanguifluus in the present study found to be between 250 and 400 nm for azulene and its derivatives as in the study of Matênovâ et al (2014) [50]. It is thought that major colorants in the edible Lactarius species could be azulene and its derivatives.…”
Section: Spectrophotometric Analysissupporting
confidence: 77%
“…To examine absorbance properties of L. deliciosus and L. sanguifluus crude extracts, the adsorption UV-Vis spectra were measured and the obtained spectra in full UV-Vis range are presented in Figure 3. The absorption spectra of natural dyes from L. deliciosus and L. sanguifluus in the present study found to be between 250 and 400 nm for azulene and its derivatives as in the study of Matênovâ et al (2014) [50]. It is thought that major colorants in the edible Lactarius species could be azulene and its derivatives.…”
Section: Spectrophotometric Analysissupporting
confidence: 77%
“…According to the previous research by Beigi et al [ 41 , 67 , 75 ], peppermint, yarrow and chamomile are herbs with high contents of terpenes, terpenoids and phenolic compounds, which was confirmed by the peak registered at the 270 nm and as a band for 290–320 nm [ 90 , 91 , 92 ]. The chlorophyll content characteristic for plants was noticed as an extensive peak in the range of 360 to 450 nm and at 680 nm [ 93 ].…”
Section: Resultsmentioning
confidence: 95%
“…The azulene molecule consists of two condensed rings, cyclopentadiene and cycloheptatriene, and possesses 10π electrons, so it obeys Hückel's rule. Moreover, azulene with its deep blue color is isomeric with colorless naphthalene and intensively absorbs light in the range of 500-700 nm [17,18].…”
Section: Introductionmentioning
confidence: 99%